Aerodynamic and Stealth Integrated Design of DSI Inlet by Surrogate-Based Multi-Objective Optimization with EHVI Infill Criterion (Xibei Gongye Daxue Xuebao, 2019)
To deal with the problem of aerodynamic and stealth integrated optimization of DSI inlet, a multi-objective optimization study on aerodynamic and stealth of the DSI inlet is carry out which based on the deformation of the three-dimensional compression bump surface. The FFD parametric method is used to parameterize the bump surface; CFD calculation based on RANS equations is used to analyze the aerodynamic performance of the DSI inlet, large element physical optical method and uniform theory of diffraction are used to calculate RCS of the DSI inlet; And ASMOPSO algorithm with the Kriging surrogate model which based on the expect hyper-volume improvement infill criterion is adopted for integrated optimization design. The results of DSI inlet aerodynamic and stealth integrated optimization exhibit considerable improvement.